Photoactive Molecular‐Based Devices, Machines and Materials: Recent Advances. Issue 42 (2nd November 2018) - Baroncini, Massimo; Canton, Martina; Casimiro, Lorenzo; Corra, Stefano; Groppi, Jessica; La Rosa, Marcello; Silvi, Serena; Credi, Alberto
Abstract: Invited for the cover of this issue is the group of Alberto Credi from Università di Bologna and Consiglio Nazionale delle Ricerche, Italy. The cover image shows a multiphotochromic molecule and its configurational isomers, which can be reversibly interconverted by light in solution and in the solid state. Abstract : We dream that our nanodevices will, one day, harness solar energy for the wealth of mankind … Read more about the story behind the cover in the Cover Profile and about the research itself in theMicroreview by A. Credi et al.